Subsoil Potassium in Central Iowa Soils: Status and Future Challenges. Issue 1 (22nd August 2018) - Obrycki, John F.; Kovar, John L.; Karlen, Douglas L.
Abstract : Core Ideas: Surface and subsurface soil K concentrations are both important. Soil‐test K levels in many central Iowa soils are below recommended levels. A cellulosic‐based bioeconomy will require higher soil‐test K concentrations. Plant‐available K below 15 cm averaged 100 to 110 mg kg ‐1 in central Iowa. A reevaluation of plant‐available K within central Iowa soils is needed, especially if crop residues are harvested for animal feed or cellulosic feedstock. This study evaluated plant‐available K concentrations to depths of 120 cm ( n = 2433) within soil profiles at 10 experimental sites. Data from 0‐ to 5‐, 5‐ to 15‐, 0‐ to 15‐, 15‐ to 30‐, 30‐ to 60‐, 60‐ to 90‐, and 90‐ to 120‐cm depths were compiled and evaluated. Based on over 400 samples collected from each depth increment below 15 cm, a reference value of 100 mg kg –1 appears common for central Iowa subsoils. Sixty‐four percent of all samples had soil‐test K levels below the 120 mg kg –1 threshold for very low nutrient status for crop production in Iowa. Only 28% of surface soil samples (<15‐cm depth) were considered to have at least optimum nutrient status with concentrations greater than 160 mg kg –1 . As K is not an environmentally sensitive nutrient, its management in central Iowa soils has generally been neglected in recent years, particularly when compared with N and P management initiatives. Building awareness of soil K profile concentrations, rather than focusing only on surface concentrations, will be necessary to meet nutrient requirements for 21st century agricultural production.